Anterior superior alveolar nerve injury after extended endoscopic medial maxillectomy: a preclinical study to predict neurological morbidity. Issue 10 (14th August 2017) - Schreiber, Alberto; Mattavelli, Davide; Ferrari, Marco; Rampinelli, Vittorio; Lancini, Davide; Ravanelli, Marco; Bertazzoni, Giacomo; Rodella, Luigi Fabrizio; Buffoli, Barbara; Doglietto, Francesco; Nicolai, Piero
Abstract : Background: Endoscopic medial maxillectomies (EMMs) are used to optimize exposure of the maxillary sinus and retromaxillary areas. Although in type D EMM (Sturmann‐Canfield procedure) the anterior superior alveolar nerve (ASAN) is always at risk of injury, only 29% of patients complained of alveolar process and dental anesthesia. The purpose of this anatomical study is to assess the neural anastomotic network of the ASAN (ASAN‐NAN) and describe different extensions of type D EMMs in a preclinical setting. Methods: The ASAN and its medial anastomotic branches (MABs) and lateral anastomotic branches (LABs) were evaluated by cone‐beam computerized tomography (CBCT). Five different extensions of type D (D1 to D5) EMMs were identified and nerves at risk of injury in each type were assessed by CBCT. Moreover, quantification of surgical corridors was performed on cadaver heads with a neuronavigation system. Results: Fifty‐seven CBCT scans were analyzed. The ASAN would be spared in 16.3% of cases with a type D1 EMM, while it would be injured in the majority of type D2 to D5 resections. At least 1 nerve of the ASAN‐NAN was spared in 96.6%, 93%, 74.6%, 0%, and 65.8% of type D1 to D5 EMMs, respectively. Two cadaver heads were dissected and the incremental volume and number of maxillary subsites exposed was assessed in type D1 to D5 EMMs. Conclusion: ASAN function impairment is probably compensated by LABs and MABs. If this hypothesis will be validated in a prospective study on patients, preoperative CBCT evaluation could predict neurological morbidity after type D EMM, and allow tailoring the procedure to minimize impairment of the ASAN‐NAN.